Os impactos das cooperativas de agricultura familiar na sustentabilidade dos seus cooperados nos municípios de Umuarama e Dois Vizinhos - PR - Oliveira, Willer Carlos de (2022)
The process of globalization that acts through its webs, permeates world trends, and in societies, requires new forms and alternatives of organization. The reality of the market and its economic and educational links also present new perspectives, potentialities and challenges, which require the effective participation of people in the search for viable and environmentally correct economic alternatives. Family farming cooperatives present ways of helping each other to solve common desires, creating opportunities from the influence on their activities with the cooperative members. This dissertation has as main objective to analyze the impacts of the actions of family farming cooperatives on the sustainability of rural producers in the municipalities of Umuarama and Dois Vizinhos in Paraná. In order to meet the objectives proposed in this study, an exploratory-descriptive type of research was carried out, in which research was carried out in the Web of Science database. The results permeate between four main focuses in the analyzed articles, namely: perception of farmers, cooperative practices, quality of life and management and satisfaction, which directly impact the sustainability of their cooperative members. A questionnaire was applied to the cooperative members. It was found that cooperative farmers in the municipality of Dois Vizinhos, southwest of Paraná, have a greater relationship with their cooperatives, especially the CLAF and COAFAR cooperatives, also due to being in a region focused and organized in cooperativism, actions with cooperatives are carried out in a healthier and more direct way, through contacts, meetings, training, technical assistance, assemblies and others. Regarding cooperative practices, in the view of the cooperative members of the two municipalities, these practices are indifferent to their sustainability, thus, it is important to observe if the cooperative discloses these actions, if it allows access to all, and if it has the participation and understanding of all its members. With regard to quality of life and management, the associates observe whether the cooperatives contribute to social involvement, interaction, integration and solidarity among the cooperative members, improve the quality of life and well-being of the farmers, help in the survival of crops of small properties, the adoption of management practices, systems and applications by the cooperative members is favored, and the cooperative members are involved in decision-making at meetings and assemblies, thus generating sustainability in the quality of life and management. Regarding the indicator on the satisfaction of its members, the actions of cooperatives have a direct impact on the sustainability of their members, since these actions are generating profitability and partnership with their members.